Newsletter no. 43 - International Commission on the History of Geological Sciences; Cooper, B. J. (My University, 2011)
INHIGEO produces an annual publication that includes information on the commission's activities, national reports, book reviews, interviews and occasional historical articles.
Keywords: Geology -- History -- Congresses